Joe Sneed, in memoriam - Moulines, C. Ulises (Universidad Nacional de Quilmes, 2020)
Fil: Moulines, C. Ulises. Ludwig-Maximilians-Universität München. Seminar für Philosophie, Logik und Wissenschaftstheorie; Alemania.